Les éléments du récit personnel dans les échanges en ligne portant sur les sujets d’actualité : raconter pour mieux comprendre, reprendre pour entrer en dialogue - Górecka, Joanna (Studia Romanica Posnaniensia, 2019)
The paper aims to present the potential, for foreign language students, of the exolingual interactions online in public and open forums. For the analysis of students’ commentaries, I apply the observation categories that were first elaborated for the analysis of posts published in press sites. I focus on narrative commentaries in which web users organize phenomena and events discussed in public discourse and try to give them their individual interpretation. I consider this kind of interaction on press sites as contributing to the civic debates: I argue that they can be also integrated in observation categories used to describe and analyze exchanges between students discussing social issues in reference to foreign language media information. In the paper I present two kinds of commentaries: those written by native speakers in public forums and those written by FL students in response to public commentaries.